2019
DOI: 10.1038/s41467-019-12780-8
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomic atlas of the human retina identifies cell types associated with age-related macular degeneration

Abstract: Genome-wide association studies (GWAS) have identified genetic variants associated with age-related macular degeneration (AMD), one of the leading causes of blindness in the elderly. However, it has been challenging to identify the cell types associated with AMD given the genetic complexity of the disease. Here we perform massively parallel single-cell RNA sequencing (scRNA-seq) of human retinas using two independent platforms, and report the first single-cell transcriptomic atlas of the human retina. Using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
238
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(253 citation statements)
references
References 42 publications
15
238
0
Order By: Relevance
“…The loss of NMNAT2 induces an increase in NMN that is hypothesized to activate SARM1-dependent axon degeneration 53,54 . Our metabolomic analysis revealed that NMN is increased in the NMNAT1-deficient retinas ( Figure 1D), and previous studies have detected SARM1 in mouse and bovine photoreceptor cells [55][56][57] . These results raise the possibility that the increased retinal NMN activates SARM1 and induces NAD + loss and cellular degeneration in the retina.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The loss of NMNAT2 induces an increase in NMN that is hypothesized to activate SARM1-dependent axon degeneration 53,54 . Our metabolomic analysis revealed that NMN is increased in the NMNAT1-deficient retinas ( Figure 1D), and previous studies have detected SARM1 in mouse and bovine photoreceptor cells [55][56][57] . These results raise the possibility that the increased retinal NMN activates SARM1 and induces NAD + loss and cellular degeneration in the retina.…”
Section: Resultssupporting
confidence: 86%
“…Finally, we defined the molecular mechanism by which NMNAT1 promotes photoreceptor function and survival. In Single-cell transcriptomic RNA analysis also found Nmnat1 in rods and cones 57,61 . Consistent with an extranuclear role for NMNAT1 in photoreceptors in these studies, cytosolic NMNAT2 was either not identified or was found at much lower levels than NMNAT1.…”
Section: Discussionmentioning
confidence: 84%
“…Single-cell RNA sequencing (scRNA-seq) is a powerful tool to study development, tissue, and disease biology [1][2][3][4][5][6][7][8][9] . scRNA-seq analyses currently rely on the availability of high quality genome annotations to define cell features and to perform cell clustering, dimensionality reduction, differential gene expression, and other analyses [10][11][12][13][14] . Identifying genes and correctly annotating their locations and coding regions within the genome is a difficult task that collaborative projects such as Ensembl, ENCODE, and GENCODE are striving to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…As an extension of the CNS, the retina is a commonly used model to study different neuron types [16]. The retina is composed of several neuron types that are well characterized from early development through adult stages [17][18][19][20][21][22][23][24][25][26][27]. Within the retina, the RGCs primarily relay visual information to the brain [28].…”
Section: Introductionmentioning
confidence: 99%